2014
DOI: 10.1371/journal.pone.0114639
|View full text |Cite|
|
Sign up to set email alerts
|

The Release Rate of Environmental DNA from Juvenile and Adult Fish

Abstract: The environmental DNA (eDNA) technique is expected to become a powerful, non-invasive tool for estimating the distribution and biomass of organisms. This technique was recently shown to be applicable to aquatic vertebrates by collecting extraorganismal DNA floating in the water or absorbed onto suspended particles. However, basic information on eDNA release rate is lacking, despite it being essential for practical applications. In this series of experiments with bluegill sunfish (Lepomis macrochirus), we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
339
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(380 citation statements)
references
References 21 publications
28
339
3
Order By: Relevance
“…For example, in an aquarium study of Idaho giant salamanders (Dicamptodon aterrimus), rate of eDNA production related positively to salamander biomass (Pilliod et al 2014). A similar trend of eDNA production positively related to biomass was observed in Bluegill Sunfish (Maruyama et al 2014). However, when corrected Conserv Genet (2016) 17:1-17 3 for biomass, juvenile Bluegill Sunfish released eDNA at a higher rate than adults (target amplicon copies per hour per gram fish body weight), leading the authors to conclude that ontogenetic factors such as changes in behavior and metabolism influence eDNA production.…”
Section: Introductionmentioning
confidence: 62%
“…For example, in an aquarium study of Idaho giant salamanders (Dicamptodon aterrimus), rate of eDNA production related positively to salamander biomass (Pilliod et al 2014). A similar trend of eDNA production positively related to biomass was observed in Bluegill Sunfish (Maruyama et al 2014). However, when corrected Conserv Genet (2016) 17:1-17 3 for biomass, juvenile Bluegill Sunfish released eDNA at a higher rate than adults (target amplicon copies per hour per gram fish body weight), leading the authors to conclude that ontogenetic factors such as changes in behavior and metabolism influence eDNA production.…”
Section: Introductionmentioning
confidence: 62%
“…Understanding variability in DNA shedding rates across species will also strengthen quantitative estimates (Maruyama et al . 2014; Klymus et al . 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Once the water is collected, it should be filtered and stored as soon as possible since the quality and quantity of DNA present in water decreases rapidly (Thomsen et al 2012a;Maruyama et al 2014). For example, Maruyama et al (2014) observed detectable concentrations of bluegill fish (Lepomis macrochirus) to decline by half in under 7 h at 20 o C. Even when unfiltered water is frozen at -20 o C, reductions of amplifiable DNA as great as ten-fold are reported in the literature (Cornelisen et al 2012).…”
Section: Extraction Of Dna From Water and Icementioning
confidence: 99%
“…For example, Maruyama et al (2014) observed detectable concentrations of bluegill fish (Lepomis macrochirus) to decline by half in under 7 h at 20 o C. Even when unfiltered water is frozen at -20 o C, reductions of amplifiable DNA as great as ten-fold are reported in the literature (Cornelisen et al 2012). Therefore, it is preferable to filter samples as soon as possible after sampling, and to preserve the filtered material at low temperature; studies have shown filters (and associated DNA) can be stored at -20 o C for later DNA extraction without significant loss of amplifiable DNA (Gilpin et al 2013).…”
Section: Extraction Of Dna From Water and Icementioning
confidence: 99%